Sebaceous carcinoma - Rakhi ISSRANI; Vaishali KELUSKAR; Santosh PATIL; Namdeo PRABHU (International Arab Journal of Dentistry (IAJD), 2016)
Chronic non-healing ulcers of the skin are a manifestation of many different pathologic processes, caused by local and/ or systemic factors. The causes range from vascular disease and diabetes to foreign bodies, malignancy, infections, and unknown causes. Basal cell carcinoma and squamous cell carcinoma are the most commonly encountered in the orofacial region. Sebaceous carcinoma is a rare and potentially aggressive tumor that rarely occurs in the face and scalp with a non-specific clinical presentation. In the present paper, we describe a case of sebaceous carcinoma in a 62-year-old male patient on the right side of the face, evolving as a non-healing ulcer since six months. The etiology of the present case seems to be multifactorial; the clinical history included a trauma, ultraviolet radiation and medications intake.